Level of Students Conceptual Understanding and Resource Theory View: Geometric Optics - Hilma Wahyuni, Ike; Reyza Arief Taqwa, Muhammad (Yayasan Nurul Yakin Bunga Tanjung, 2022)
This study aims to identify the level of understanding (LoU) and resources that students activate. This is a descriptive study. The study used a survey method by distributing ten multiple-choice questions. The focus of the study is geometric optics. The research was conducted on 64 physics students who were taking Basic Physics III courses. Data analysis was carried out by determining descriptive statistics and categorizing students' LoU based on the reasons given. The LoU includes Sound Understanding, Partial Understanding, Partial Understanding with Specific Misconceptions, Specific Misconceptions, and Not Understanding. Based on the analysis of the research results, the average score of students' conceptual understanding was 53.44. Furthermore, the average levels of understanding are 15.9% for Sound Understanding, 28.1% for Partial Understanding, 14.7% for Partial Understanding with Specific Misconceptions, 16.4% for Specific Misconceptions, and 26.2% for Not Understanding. Meanwhile, the resource that is activated by students when showing possible rays in the formation of images on a convex lens is